Finding the declarative tipping point XQuery, XML and the RDBMS. - Kershaw, David
Moving information from a database into an application may be the most common challenge developers face. How many of us make it through life without meeting object/relational (O/R) mapping in some form? Certainly not too many. Lately it has become equally difficult to avoid XML/relational (X/R) mapping. Because XML, and especially XML Schemas (XSD), are object like paradigms, the mapping difficulty is approximately the same. However, under the ever expanding influence of XML, the extract, transform, load process that gets data from a database into an application (and vice versa) may be about to get radically more simple and declarative.